2022
DOI: 10.1111/tops.12597
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spatial Perspective Taking: Analysis of Four Measures Using Item Response Theory

Abstract: Research on spatial thinking requires reliable and valid measures of individual differences in various component skills. Spatial perspective taking (PT)—the ability to represent viewpoints different from one's own—is one kind of spatial skill that is especially relevant to navigation. This study had two goals. First, the psychometric properties of four PT tests were examined: Four Mountains Task (FMT), Spatial Orientation Task (SOT), Perspective‐Taking Task for Adults (PTT‐A), and Photographic Perspective‐Taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 99 publications
1
16
1
Order By: Relevance
“…However, we did show significant association between GM volume and scores on the PPT in lobule VI. This result and the absence of other significant correlations, notably with tests assessing specific memory processes, could be also explained by the capacity of the PPT to reflect multiple facets of cognition [ 28 , 29 ]. Previous studies have shown that the performance of older adults in navigational tasks could be predicted by PPT scores but not by executive or memory scores [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did show significant association between GM volume and scores on the PPT in lobule VI. This result and the absence of other significant correlations, notably with tests assessing specific memory processes, could be also explained by the capacity of the PPT to reflect multiple facets of cognition [ 28 , 29 ]. Previous studies have shown that the performance of older adults in navigational tasks could be predicted by PPT scores but not by executive or memory scores [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This task required participants to visualize what photographs would look like when taken from cameras placed at different positions and angles relative to their viewpoint. The original task was designed for children, thus the version used in the present study was adapted in difficulty level for use in adult populations (Brucato et al, 2022). In each item, participants were shown an image of a toy character near an arrangement of three objects.…”
Section: Psychometric and Self-report Measuresmentioning
confidence: 99%
“…Each of the eight angular differences (0°, 180°, to the right 45°, 90° or 135°, and to the left 45°, 90° or 135°) was presented four times. Accuracy was recorded on the computer through the participants' click selection for each item scores were calculated at the total number of items correctly answered out of the total time it took them to complete the task (Brucato et al, 2022).…”
Section: Psychometric and Self-report Measuresmentioning
confidence: 99%
“…Yet, it remains difficult to find validated measures for many specific types of spatial abilities (cf. Brucato et al 2022 ; Newcombe et al 2023 ), especially if they need to be suitable for young children or group testing. Many of the existing measures that closely model tests originally developed for adults are difficult to understand for young children or preschoolers.…”
Section: Introductionmentioning
confidence: 99%